The Adequacy of the Enterprise Resources Planning (ERP) Systems for the Creation of Intangible Managerial Accounting Information: an exploratory study - Antunes, Maria Thereza Pompa; Alves, Alex Serafim (Review of Business Management, 2008)
The general objective of this work was to study the contribution of the ERP for the quality of the managerial accounting information, through the perception of managers of large sized Brazilian companies. The initial principle was that, presently, we live in an enterprise reality characterized by global and competitive worldwide scenery where the information about the enterprise performance and the evaluation of the intangible assets are necessary conditions for the survival of the companies. The research of the exploratory type is based on a sample of 37 managers of large sized Brazilian companies. The analysis of the data treated by means of the qualitative method showed that the great majority of the companies of the sample (86%) possess an ERP implanted. It also showed that this system is used in combination with other applicative software. The managers, in its majority, were also satisfied with the information generated in relation to the dimensions Time and Content. However, with regard to the qualitative nature of the information, the ERP made some analysis possible when the Balanced Scorecard was adopted, but information able to provide an estimate of the investments carried through in the intangible assets was not obtained. These results suggest that in these companies ERP systems are not adequate to support strategic decisions. Key-words: Enterprise Resource Planning ERP. Accounting information. Intangible assets.